A possible pathway for rapid growth of sulfate during haze days in China - Li, Guohui; Bei, Naifang; Cao, Junji; Huang, Rujin; Wu, Jiarui; Feng, Tian; Wang, Yichen; Liu, Suixin; Zhang, Qiang; Tie, Xuexi; Molina, Luisa T. (Atmospheric chemistry and physics, 2017)
Rapid industrialization and urbanization have caused frequent occurrence of haze in China during wintertime in recent years. The sulfate aerosol is one of the most important components of fine particles (PM2. 5) in the atmosphere, contributing significantly to the haze formation. However, the heterogeneous formation mechanism of sulfate remains poorly characterized. The relationships of the observed sulfate with PM2. 5, iron, and relative humidity in Xi'an, China have been employed to evaluate the mechanism and to develop a parameterization of the sulfate heterogeneous formation involving aerosol water for incorporation into atmospheric chemical transport models. Model simulations with the proposed parameterization can successfully reproduce the observed sulfate rapid growth and diurnal variations in Xi'an and Beijing, China. Reasonable representation of sulfate heterogeneous formation in chemical transport models considerably improves the PM2. 5 simulations, providing the underlying basis for better understanding the haze formation and supporting the design and implementation of emission control strategies.